Retail trade international - Euromonitor (London : Euromonitor Publications, 1980)
This volume features statistics on retail trends in 36 countries throughout the world.
includes appendixes
ijb, 17/01/2019
Loans
Keywords: Commerce-Trade; Retail trade; Einzelhandel; Prognose; Welt; Retail trade; Statistics